Correlation of Neutrophil-Lymphocyte Ratio and Critical Illness in Adults on Vancomycin: A Cross-Sectional Study - Alfhili MA; Alazmi SA; Alsughayyir JM (International Journal of General Medicine)
Mohammad A Alfhili, Sahar A Alazmi, Jawaher Mohammad Alsughayyir Department of Clinical Laboratory Sciences, College of Applied Medical Sciences, King Saud University, Riyadh, 12372, Saudi ArabiaCorrespondence: Mohammad A Alfhili, Department of Clinical Laboratory Sciences, College of Applied Medical Sciences, King Saud University, Riyadh, 12372, Saudi Arabia, Email malfeehily@ksu.edu.saBackground: Early risk-stratification in patients receiving vancomycin (VAN) is crucial but reliable markers are scarce. Herein, the correlates and determinants of neutrophil-lymphocyte ratio (NLR), an emerging inflammatory marker, with ICU admission in VAN-treated adults were investigated.Methods: Demographic and clinical data for 295 adults treated with VAN at King Khalid University Hospital from January 2024 to February 2025 were retrospectively analyzed using Mann–Whitney U and Chi-square tests, Spearman rank correlation, regression analysis, effect size measures, and calculation of areas under the receiver operating characteristic curve (AUC).Results: NLR was significantly elevated in ICU compared to non-ICU patients (p < 0.0001) and the proportion of ICU patients with elevated NLR was significantly higher than those with normal NLR (X2 = 33.69, p < 0.0001) irrespective of age or gender. In particular, ICU requirement was 2.49 and 2.54 times more prevalent in males and females with elevated NLR, respectively (p = 0.0002). Also, ICU admission was 4.25 and 4.40 times more likely when NLR was elevated in males and females, respectively (p = 0.0001). Notably, ICU admission was independently associated with a 9.65-unit increase in NLR (p = 0.0005) of which age, body mass index, and conjugated bilirubin were identified as independent predictors. Moreover, NLR showed good diagnostic ability for ICU requirement with AUC ranging from 0.71 to 0.78 (p < 0.0001).Conclusion: NLR is easily accessible, cost-effective, and demonstrates promising potential to complement existing markers for identifying high-risk patients and optimizing early intervention in critically ill adults receiving VAN therapy.Keywords: NLR, vancomycin, ICU, inflammation, sepsis